PERAN SEKOLAH DALAM MENANAMKAN KARAKTER DISIPLIN UNTUK MENGURANGI KENAKALAN REMAJA PADA SISWA SMA NEGERI 2 BAYUNG LENCIR - Antika, Maya Nur; Usmanto, Heri; Hendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Instilling discipline in schools is a strategic effort to reduce juvenile delinquency. Discipline as a character value needs to be instilled through various aspects, including punctuality, adherence to rules, accuracy in submitting assignments, and the use of good written language. However, in practice, students are still found to lack discipline, indicating that the school's role is not yet fully optimized. This study aims to describe the school's role in instilling discipline in students and identify the inhibiting factors faced at SMA Negeri 2 Bayung Lencir. The study used a descriptive qualitative approach with a purposive sampling technique. Informants consisted of the Vice Principal for Curriculum and the Pancasila Education teacher as the main informants, as well as several students selected according to the research needs. Data were obtained through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the school's role in instilling discipline to reduce juvenile delinquency at SMA Negeri 2 Bayung Lencir has been implemented, but not optimally. The school has made various efforts through socialization of discipline, teacher supervision, sanctions, and integration of discipline values ​​in learning. In conclusion, the role of schools in instilling discipline is not yet fully optimal, as the values ​​instilled through regulations, teacher role models, and supervision are not fully reflected in student behavior. Therefore, discipline still needs to be strengthened to foster an orderly school culture and contribute to reducing juvenile delinquency.